Ethical, Environmental, and Sustainable Management in Corporate Responsibility: A Systematic Review - Surendra Prasad Joshi; Mamata Prajapati; Ramchandra Adhikari (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
The economic system of today's world has two different avenues that lead either in the development of capital assets or the implementation of ethical business practices. Businesses are now facing challenges for the evaluation because they are required to present the interrelationship between their ethical business practices and their sustainable operation methods. This research study examines the "integration gap" which describes the non-linear process through which abstract ethical concepts in CSR develop into measurable results. The systematic review examines worldwide research evidence that studies the relationship between ethical practices and green initiatives because this relationship affects various areas of organizational performance. The research identification process, which follows PRISMA guidelines, resulted in selecting 20 important studies from 700 research records that existed in five major scientific databases, including Scopus and Web of Science. The synthesis establishes ethical principles as the fundamental structural component that drives all aspects of sustainability. Corporate social responsibility creates an indirect relationship with business performance, which executives use multiple strategic pathways, including green innovation, environmental strategy and transformational leadership. The success of international corporate social responsibility practices depends on two factors: how stakeholders participate and how companies implement corporate social responsibility practices. The research results establish a "dual-benefit" model, showing that ethical governance yields two outcomes: improved operational efficiency and a unique green corporate identity. The review presents an innovative mechanistic mapping system that includes a mediator taxonomy that helps practitioners secure sustainable competitive benefits through ethical compliance. Future research should focus on industrial sectors that currently lack representation and use longitudinal study methods.